Vygotsky’s Defectology: A Misleading Term for a Great Conception - Giest, Hartmut (Educação, 2018)
Although defectology is a misleading term (suggesting the opposite of its meaning) it is a great conception offering solutions to a lot of problems tied to inclusion as a demand of modern society. Therefor I will 1) disclose the theoretical roots of the conception, 2) trace its historical development in order to show how it was misunderstood, 3) apply the conception to inclusion and 4) demonstrate some practical examples showing that the conception is also important for educational practice – among other things by helping to close the gap between theory and practice. *** Defectologia de Vygotsky: um termo equivocado para uma grande concepção *** Embora defectologia seja um termo equivocado (sugerindo o contrário do seu significado), é uma grande concepção que oferece soluções para muitos problemas ligados à inclusão como uma demanda da sociedade moderna. Por isso vou 1) revelar as raízes teóricas da concepção, 2) traçar o seu desenvolvimento histórico, a fim de mostrar como foi mal interpretado, 3) aplicar a concepção à inclusão e 4) demonstrar alguns exemplos práticos que mostram que a concepção também é importante para prática educacional – entre outras coisas, ajudando a fechar a lacuna entre teoria e prática. Palavras-chave: Psicologia; Educação; Vygotsky; Defectologia.